Cohesive zone length of orthotropic materials undergoing delamination. (July 2016) - Soto, A.; González, E.V.; Maimí, P.; Turon, A.; Sainz de Aja, J.R.; de la Escalera, F.M.
Highlights: Literature review of the analytic and numerical studies to determine the cohesive zone length. Numerical parametric study to discuss the range of applicability of the existing formulas. Novel expressions are proposed to predict the cohesive zone length under pure fracture modes. Abstract: Polymer-based laminated composite materials can fail by delamination. Cohesive zone development occurs during delamination, where dissipation mechanisms take place. Within a numerical framework, a fine discretization is needed along the cohesive zone length to accurately capture the non-linear stress distribution. Knowing the cohesive zone length beforehand is important for meshing purposes. This paper presents a literature review of existing analytic expressions. The limitations and range of applicability of the analytic formulas are discussed. Novel empirical formulas are proposed to predict the cohesive zone length of homogeneous orthotropic materials with a crack growing under pure mode I or pure mode II.